2008
DOI: 10.1093/jxb/ern129
|View full text |Cite
|
Sign up to set email alerts
|

Sugar beet contains a large CONSTANS-LIKE gene family including a CO homologue that is independent of the early-bolting (B) gene locus

Abstract: Floral transition in the obligate long-day (LD) plant sugar beet (Beta vulgaris ssp. vulgaris) is tightly linked to the B gene, a dominant early-bolting quantitative trait locus, the expression of which is positively regulated by LD photoperiod. Thus, photoperiod regulators like CONSTANS (CO) and CONSTANS-LIKE (COL) genes identified in many LD and short-day (SD)-responsive plants have long been considered constituents and/or candidates for the B gene. Until now, the photoperiod response pathway of sugar beet (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 66 publications
(105 reference statements)
2
99
1
1
Order By: Relevance
“…In both monocots and dicots the COL (CONSTANS-Like) family has many members such as 17 in Arabidopsis, 16 in rice, 9 in barley (Griffiths et al 2003), 10 in sugarbeet (Chia et al 2008), 11 in Medicago (Wong et al 2014), 26 in soybean (Wu et al 2014) and 23 in cotton (Zhang et al 2015). All of these COL genes are characterized by the presence of three domains namely the B-box 1, B-box 2 and a CCT (CO, COlike, and TOC1) domain (Griffiths et al 2003;Putterill et al 1995;Strayer et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both monocots and dicots the COL (CONSTANS-Like) family has many members such as 17 in Arabidopsis, 16 in rice, 9 in barley (Griffiths et al 2003), 10 in sugarbeet (Chia et al 2008), 11 in Medicago (Wong et al 2014), 26 in soybean (Wu et al 2014) and 23 in cotton (Zhang et al 2015). All of these COL genes are characterized by the presence of three domains namely the B-box 1, B-box 2 and a CCT (CO, COlike, and TOC1) domain (Griffiths et al 2003;Putterill et al 1995;Strayer et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Group II contains B-box1, a less conserved or diverged B-box2 and CCT domain but lacks the VP motif while Group III contains B-box 1 and CCT domain only (Gangappa and Botto 2014;Zhang et al 2015). In a broader way COL proteins are a part of the BBX family transcription factors with diverse functions (Almada et al 2009;Chia et al 2008;Crocco and Botto 2013;Datta et al 2006;Huang et al 2012;Valverde 2011). The characterization and analysis of Group I CO genes has been carried out in many plant species and these cluster with Arabidopsis CO and rice Hd1 (Gangappa and Botto 2014;Griffiths et al 2003;Huang et al 2012;Zhang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, overexpression of PpCOL-1 with 35S::CO will be able to restore the late flowering phenotype of co-1 or co-2, which can suggest that PpCOL-1 has the same function as CO in arabidopsis. Similar studies have been conducted to CO and CO-like isolated in other plants species such as poplar (CO1 and CO2) (Hsu et al, 2012) and sugarbeet (BvCOL1) (Chia et al, 2008). In these studies, overexpression of the COLs was able to restore the late flowering phenotype of co mutants in arabidopsis.…”
Section: Limitations and Future Directionssupporting
confidence: 67%
“…Heading Date 1 (Hd1), a CO-like homologue gene in rice, has significant sequence similarity to the Arabidopsis gene and plays a role in photoperiod regulation of flowering through the FT homologue Heading Date 3 (Hd3) gene activation (Yano et al, 2000;Kojima et al, 2002). A study in sugar beet (Beta vulgaris) has found that the CO homologue gene BvCOL1 plays a part in photoperiodic response, as overexpression of this gene in the Arabidopsis co-2 mutant restored the late flowering phenotype (Chia et al, 2008).…”
Section: Timing Of Cab Expression (Cct)mentioning
confidence: 99%
See 1 more Smart Citation